UJI DISOLUSI DAN PENETAPAN KADAR TABLET AMLODIPIN 5 mg GENERIK DAN BERMEREK - khasanah, kharismatul (BENZENA Pharmaceutical Scientific Journal, 2025)
Hypertension is a significant health issue with a prevalence of 34.1% in Indonesia, yet many individuals with hypertension do not consistently take medication. Amlodipine, an antihypertensive and antianginal drug belonging to the calcium channel blocker class, is widely used in both generic and branded forms. The differences between these two are often considered when choosing treatment, as generic drugs are more affordable, although their quality is frequently questioned. Generic drugs are often perceived as inferior to branded or innovator drugs. Therefore, research is needed to ensure that the quality of generic drugs is not lower than that of branded products. This study aims to compare the quality of generic and branded amlodipine tablets through weight uniformity testing, content determination, and dissolution testing. A descriptive research method was used. The weight uniformity test was performed by weighing 20 tablets from each sample. The dissolution test was conducted using a paddle-type apparatus (method 2). Content determination was performed using UV-Vis spectrophotometry at a wavelength of 237 nm to determine the amlodipine content in the tablets. Data obtained were analyzed using Microsoft Excel. The results showed that both generic and branded amlodipine tablets met the dissolution test requirements according to the Indonesian Pharmacopoeia (Edition VI), with at least 50% dissolution within 30 minutes as indicated on the label. The dissolution profiles of both generic and branded amlodipine tablets showed similar drug release patterns. However, the dissolution efficiency (DE) for both samples was relatively low, with DE values at the 5-minute mark being 9.52% for the generic tablet and 10.32% for the branded tablet. At the 30-minute mark, the dissolution efficiency for both samples reached approximately 33%.